POTENSI AROMATERAPI DAN AKUPRESUR SEBAGAI INTERVENSI NON-FARMAKOLOGIS UNTUK MEREDUKSI KECEMASAN PADA IBU HAMIL: TINJAUAN LITERATUR SISTEMATIS TERHADAP STUDI KLINIS TERKINI - Yulizawati, Yulizawati; Aprila, Prety Zinta; Ridwan, Laila Hijradesy; Amira, Suci (Poltekkes Kemenkes Bandung, 2025)
Anxiety during pregnancy is a prevalent global health concern affecting 15–23% of pregnant women and is associated with adverse outcomes such as preterm birth and impaired fetal development. Non-pharmacological therapies, including aromatherapy and acupressure, have gained popularity due to their low risk of side effects and cost-effectiveness compared to pharmacological interventions. This study aimed to systematically review recent clinical evidence on the efficacy and safety of these therapies in reducing anxiety among pregnant women. This systematic literature review adhered to PRISMA guidelines, with searches conducted across Wiley Online Library, Google Scholar, PubMed, Science Direct, and Taylor & Francis databases from 2014 to 2024. Keywords included “aromatherapy,” “acupressure,” “anxiety,” and “pregnancy.” Out of 1,614 identified articles, 12 studies met inclusion criteria based on PICOS framework. Study quality was assessed using AMSTAR and the Cochrane Risk of Bias Tool. Aromatherapy significantly reduced anxiety levels through modulation of the limbic system and increased serotonin release. Acupressure applied at specific points was also effective by stimulating endorphin release. Both therapies demonstrated a favorable safety profile without serious adverse effects. Clinical studies conducted in Indonesia further support the feasibility of implementing these interventions within local midwifery care settings. However, protocol heterogeneity and small sample sizes warrant further standardized, large-scale research. Aromatherapy and acupressure are effective, safe, and affordable non-pharmacological interventions for reducing anxiety in pregnant women. Their integration into maternal and child health services requires development of standardized operational procedures, healthcare provider training, and further research to validate long-term efficacy.